2022
DOI: 10.1186/s41937-022-00099-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender effects of the COVID-19 pandemic in the Swiss labor market

Abstract: We study the impact of the pandemic on gender gaps in labor market outcomes in Switzerland. Using the Swiss Labor Force Survey data, we document a significant increase in the gender gap in labor market participation. We find no evidence of a worsening of the unemployment gender gap during the pandemic, but we find that women were more likely to uptake short-time work (STW). Unlike the USA, the presence of children in the household did not worsen labor gender gaps. Sector and occupation, however, play an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Previous studies found that increased childcare led to reduced working hours and forced women to exit the labor market [7,11,18,37]. Dubois [38] found contrary results, as women are more concentrated in part-time jobs that enable them to take care of children. Work arrangements during the pandemic highly predicted the likelihood of losing jobs among women.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies found that increased childcare led to reduced working hours and forced women to exit the labor market [7,11,18,37]. Dubois [38] found contrary results, as women are more concentrated in part-time jobs that enable them to take care of children. Work arrangements during the pandemic highly predicted the likelihood of losing jobs among women.…”
Section: Discussionmentioning
confidence: 95%
“…Tverdostup [ 36 ] and Reichelt et al [ 49 ] also found that women were more negatively affected because they had to reduce their working hours and work remotely during the pandemic. On the other hand, some studies found contradictory results that females were less likely to lose their jobs than men [ 8 ] and the pandemic did not worsen the gender gap in employment outcomes [ 18 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data that confirm that women's roles in childcare had important implications in the decline in female employment and obstacles to progress in reducing the gender gap in employment. Dubois et al (2022) analyzed the impact of COVID‐19 on gender gaps in employment in Switzerland. Although they did not observe a worsening of this during the pandemic, they did note that women were more likely to accept reductions in working hours, showing a worsening of salary results.…”
Section: State Of the Art: The Consequences Of Covid‐19 On Female Emp...mentioning
confidence: 99%
“…The rate of men married with children was not affected. Data that confirm that women's roles in childcare had important implications in the decline in female employment and obstacles to progress in reducing the gender gap in employment Dubois et al (2022). analyzed the impact of COVID-19 on gender gaps in employment in Switzerland.…”
mentioning
confidence: 99%